Association between HSV-2 and HIV serostatus in pregnant women of known HIV serostatus attending Mulago Hospital antenatal clinic, Kampala, Uganda - Sarah Nakubulwa; Florence M Mirembe; Dan K. Kaye; Deogratias Kaddu-Mulindwa (Journal of Infection in Developing Countries)
Background: Studies show that STIs such as HSV-2 increase the probability of HIV-1 acquisition and enhance transmission by increasing susceptibility and infectiousness respectively. The objective of this study was to compare the proportion of HSV-2 in HIV-positive and HIV-negative pregnant mothers attending the antenatal clinic in Mulago Teaching Hospital in Kampala, Uganda.